(untitled) (Research, Society and Development, 2020)
Pesticides or agrochemicals are groups of substances that act in the agricultural environment, in order to control different elements that harm the cultivation of plantations. Brazil is one of the largest consumers of pesticides in the world, which concerns the different sectors of health surveillance. The present work has the general objective of identifying and knowing the pathophysiological consequences of human exposure to pesticide residues. As for the methodology, it is a simple systematic review, which was carried out in August of 2020, with a bibliographic survey through electronic search of articles indexed in the Scientific Eletronic Library - Scielo, Digital Library of Theses and Dissertations of USP and Google Scholar, based on keywords: pesticides; exposure to pesticides; effects of pesticides on the physiological changes of cells; classification of pesticides, with thirty-two papers found for publication. The results obtained showed that pesticides are chemical substances with biocidal characteristics, which are used to control pests and different diseases; cause numerous intoxications that culminate in different changes in the physiological mechanism of cells, whether through digestive, respiratory, dermal and / or eye contact, which causes sets of symptoms with acute, subacute or chronic characteristics. Pesticide poisoning can be acute and chronic, and the acute one generally manifests itself in a milder or more moderate form, reaching severe cases, since the chronic causes effects of mutagenicity, carcinogenicity and reproductive toxicity in humans and animals.